Pengaturan Fan Speed dan Suhu Air Conditioner Melalui Ucapan Dengan Layanan Google Assistant API - Michael Albertus; Muliady Muliady (Universitas Tarumanagara, 2020)
Air conditioner control using speech recognition is made to help people with disabilities that unable to operate remote control physically but have verbal abilities. Verbal control allows disabled people adjust temperatures and fan speed. Speech received by Respeaker 2-mics Pi HAT module, converted into wav, processed by Google Assistant API with Natural Language Processing algorithm by categorizing words into their types, subject, predicate, object, and description to facilitate Google Assistant API. Words matched with command in command text database Raspberry Pi 3 to enable local commands modulates signal in form of space-coded signal on GPIO, transmitted through infrared transmitter to control the Air Conditioner. Infrared database obtained by receiving infrared signal through infrared receiver that have been coded by LIRC into pulse space, calling function is created, compared in command text database.The infrared light distance from the infrared transmitter can be sent to air conditioner up to 600 cm with β NPN 2N2222A transistor worth 257, Resistor base value is 1500 Ohm, and Resistor collector value is 6.2 Ohm. Speech to text experiments with background sound intensity 35-40 dB, respondent’s sound intensity 50-70dB, and the respondent’s distance to the microphone 40-50 cm. System can recognize respondent’s speeches with success rate above 50%. The word “High” in fan speed speech experiments cannot be detected by the system, so it is necessary to add other word to be recognized. The system can receive Google Translate speech and only got one failure.ABSTRAK:Perangkat elektronik air conditioner dengan pengendalian pengenalan ucapan untuk membantu penyandang tunadaksa yang tidak mampu mengendalikan remote secara fisik tetapi memiliki kemampuan verbal. Pengendalian dengan cara verbal memungkinkan penyandang tunadaksa untuk mengubah suhu dan mengatur fan speed air conditioner. Ucapan diterima modul Respeaker 2-mics Pi HAT dikonversi menjadi format wav kemudian diolah oleh Google Assistant API dengan algoritma Natural Language Processing yaitu mengategorikan kata menjadi jenisnya, subjek, predikat, objek, dan keterangannya untuk mempermudah pencarian pada kamus Google Assistant API. Kata tersebut dibandingkan dengan perintah ucapan pada commandtextdatabaseRaspberry Pi 3 yang mengaktifkan local command dan memodulasi sinyal space-coded signal pada GPIO, ditransmisikan melalui infrared transmitter untuk mengatur air conditioner. Infrareddatabase diperoleh melalui penerimaan cahaya infrared dan dikodekan menjadi pulse space oleh software LIRC menjadi fungsi pemanggilan, dipasangkan dengan perintah ucapan commandtextdatabase. Jarak cahaya infrared dari infrared transmitter dapat dikirimkan ke air conditioner hingga sejauh 600 cm dengan transistor NPN 2N2222A bernilai 257, nilai Resistor base sebesar 1500 Ohm, dan nilai Resistor collector sebesar 6,2 Ohm. Uji cobaspeech to text dengan kondisi intensitas background sound 35-40 dB, intensitas suara responden 50-70 dB, dan jarak responden ke microphone 40-50 cm. Sistem yang direalisasi mampu mengenali ucapan yang diberikan responden dengan keberhasilan di atas 50%. Ucapan “High” pada pengujian ucapan fan speed tidak dapat dideteksi oleh sistem, oleh karena itu perlu ditambahkan ucapan suhu agar ucapan dikenal. Sistem mampu menerima ucapan Google Translate dan hanya mendapatkan satu kali kegagalan deteksi ucapan